2014
DOI: 10.1111/jzo.12134
|View full text |Cite
|
Sign up to set email alerts
|

An updated description of the Australian dingo (Canis dingoMeyer, 1793)

Abstract: A sound understanding of the taxonomy of threatened species is essential for setting conservation priorities and the development of management strategies. Hybridization is a threat to species conservation because it compromises the integrity of unique evolutionary lineages and can impair the ability of conservation managers to identify threatened taxa and achieve conservation targets. Australia's largest land predator, the dingo Canis dingo, is a controversial taxon that is threatened by hybridization. Since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 30 publications
3
93
0
Order By: Relevance
“…Although the recent papers of Koler-Matznick (2003, 2007 and Crowther et al (2014) do not explicitly state the species concept followed, both studies have a strong emphasis on the differentiation of each lineage from other dogs and wolves, and on their history of genetic isolation of Dingo and New Guinea Singing Dog from each other and from other canids since their arrival in Australia and New Guinea, respectively. Both also downplay the evidence of hybridization between these 'native' dog populations and more recently introduced dog breeds, on the grounds that interspecific hybridization is common among canids and represents a shared primitive characteristic.…”
Section: Matters Of Principle-species and Domesticatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the recent papers of Koler-Matznick (2003, 2007 and Crowther et al (2014) do not explicitly state the species concept followed, both studies have a strong emphasis on the differentiation of each lineage from other dogs and wolves, and on their history of genetic isolation of Dingo and New Guinea Singing Dog from each other and from other canids since their arrival in Australia and New Guinea, respectively. Both also downplay the evidence of hybridization between these 'native' dog populations and more recently introduced dog breeds, on the grounds that interspecific hybridization is common among canids and represents a shared primitive characteristic.…”
Section: Matters Of Principle-species and Domesticatesmentioning
confidence: 99%
“…The general approaches in each case in some respects resemble those of proponents of the Phylogenetic Species Concept (PSC) which regards any diagnosable population as a potentially distinct species, but differ in that they explicitly extend this criterion to known derivatives of domestic stock. Dinets (2015) also suggested that Crowther et al (2014) used the PSC but raised concern over this species concept by suggesting that it should not be used in vertebrates as it leads to gross taxonomic inflation and has numerous theoretical shortcomings (citing Zachos & Lovari 2013).…”
Section: Matters Of Principle-species and Domesticatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction between the domestic dog and the wolf in particular is legally important and it overlaps the divide between wildlife and domestic animals. One may consider the controversies over the coyote-wolf(-dog) hybrids in North America (Morell 2016), the Australian dingo (Crowther et al 2014) or the dog-wolf, a more cosmopolitan hybrid that may be legally eliminated. 4 In some sense this discrepancy resembles the old debate on the essentialistic species concept according to which each species is characterized by its unchanging essence (eidos) and is therefore sharply separated from all other species (Mayr 1982).…”
Section: Three Phases Of De-extinctionmentioning
confidence: 99%
“…Introduced mammalian predators in Australia include the cat (Felis catus) and red fox (Vulpes vulpes). The dingo (Canis dingo, Crowther et al 2014) is not a native mammal but arrived at least 3 450 years ago (Wright and Lambert 2015), and now has a role as top mammalian predator, perhaps having taken the ecological role of similarsized extinct native carnivores Wallach et al 2010). Changed fire regimes are also considered a threat to small and mid-sized mammals (Woinarski et al 2015), potentially because intense fires interact with invasive predators, generating a 'multiplied' or synergistic negative effect (Doherty et al 2015b).…”
Section: Introductionmentioning
confidence: 99%